2018
DOI: 10.1192/bjo.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts and non-suicidal self-harm: national prevalence study of young adults

Abstract: BackgroundThere are few prevalence studies of suicide attempts and non-suicidal self-harm (NSSH).AimsWe aimed to estimate the prevalence of thoughts of NSSH, suicidal thoughts, NSSH and suicide attempts among 18- to 34-year-olds in Scotland.MethodWe interviewed a representative sample of young adults from across Scotland.ResultsWe interviewed 3508 young people; 11.3 and 16.2% reported a lifetime history of suicide attempts and NSSH, respectively. The first episode of NSSH tended to precede the first suicide at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
48
4
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 41 publications
8
48
4
7
Order By: Relevance
“…It is evident in this study that more females than males reported both lifetime and 12‐month suicidal ideations, even though the suicidal behaviour risk between females and males is comparable (Table ). This observation is consistent with previous studies in the area from high‐income countries (Aradilla‐Herrero et al, ; Leal & Santos, ) and among young people generally (Asante et al, ; Hawton et al, ; O'Connor et al, ), but contradicts the finding by Melissa‐Halikiopoulou et al () that lifetime suicidal ideations are higher among males than female nursing students in Greece.…”
Section: Discussionsupporting
confidence: 91%
“…It is evident in this study that more females than males reported both lifetime and 12‐month suicidal ideations, even though the suicidal behaviour risk between females and males is comparable (Table ). This observation is consistent with previous studies in the area from high‐income countries (Aradilla‐Herrero et al, ; Leal & Santos, ) and among young people generally (Asante et al, ; Hawton et al, ; O'Connor et al, ), but contradicts the finding by Melissa‐Halikiopoulou et al () that lifetime suicidal ideations are higher among males than female nursing students in Greece.…”
Section: Discussionsupporting
confidence: 91%
“…Entretanto, quando as taxas de suicídios efetivos entre os sexos são comparadas, homens se sobressaem em uma razão próxima de 4:1 (O'Connor et al, 2018;Sinyor et al, 2017). A diferença entre os eventos de suicídio, no que se refere aos sexos, pode ser explicada pelo fato de que os homens, por utilizarem métodos mais letais tais como armas de fogo e enforcamento, são mais efetivos do que as mulheres nas suas tentativas de pôr fim à vida; isso porque, predominantemente, elas escolhem as tentativas por envenenamento -e, geralmente, são socorridas a tempo em serviços de urgência e emergência, engrossando as estatísticas das tentativas e não as de suicídio consumado (Abreu, Silva, Kohlrausch, & Soares, 2010).…”
Section: Discussionunclassified
“…No panorama global, um em cada nove jovens tentou suicídio e um em cada seis se envolveu em autolesão sem morte (O'Connor et al, 2018). Em território brasileiro, parece haver uma tendência do agravo na população adulta jovem, que começa mais cedo nas mulheres e se estende até os 50 anos.…”
Section: Discussionunclassified
“…При этом, если подростки чаще сообщают о суицидальных мыслях и чаще практикуют несуицидальные самоповреждения, то смертей вследствие суицида больше в периоде средней взрослости [4]. Так, в недавнем крупном национальном исследовании в Шотландии, несуицидальные самоповреждения преобладали среди людей 18-23 лет, а суицидальные попытки были больше распространены у людей 30-34 лет [5].…”
unclassified
“…Несуицидальное самоповреждающее поведение (НСП) начинается в 13-15 лет или несколько ранее, его частота растёт до 25 лет, а затем идёт на спад, предположительно, уступая место более адаптивному поведению, или же, напротив, переходу в суицидальные попытки, влекущие смерть [5]. Данные по гендерным различиям противоречивы: часть исследователей пишет о преобладании НСП у девушек, часть сообщает о равной представленности обоих полов [9].…”
unclassified